Facing The Digital Era: Transforming Human Resources With Ai And Visualization Technology - Suci Rahmadani; hustin, Mirela Hikmah Hustin Naeni; sylvia, Sylvia Anggraini (Interkoneksi: Journal of Computer Science and Digital Business, 2025)
The digital era has brought significant changes in HR management through artificial intelligence (AI) and data visualization. AI improves efficiency, training and data-driven decision making, while visualization makes it easier to understand complex information and supports communications strategies. This second technology allows organizations to create human resources that are more adaptive, innovative and competent. This transformation requires innovation, continuous learning, and collaboration between humans and technology to face the challenges of the digital era effectively.